2017
DOI: 10.1039/c7ra03264a
|View full text |Cite
|
Sign up to set email alerts
|

Perylene dye-functionalized silver nanoparticles serving as pH-dependent metal sensor systems

Abstract: Lysine-functionalized perylene was used to modify nanoparticles. Due to the benefits from a synergetic effect that originated between the perylene and silver nanoparticles, color-based metal sensor systems were established. At pH ¼ 12.6, Cr 6+ with a concentration of 100 nM could be detected by a color change from deep yellow to orange; after decreasing the pH to 12.0, the detection limit decreased to 2 mM. Interestingly, after further decreasing the pH to 11.0, another kind of metal ion (Cd 2+ ) could be reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In basic media, the sensor activates the phenate oxygen-binding site in addition to the N,N,N chelate site. The ligand results a pH-dependent sensor [77], able to detect zinc(II) ion in a neutral/slightly acidic and in a slightly basic aqueous environment with different emission responses. N,N,N tridentate complexes have a part as novel polymeric materials with intriguing structural and mechanical features for the construction of smart supramolecular architectures.…”
Section: Ligands For Sensing Analysis and For Supramolecular Architecture Buildingmentioning
confidence: 99%
“…In basic media, the sensor activates the phenate oxygen-binding site in addition to the N,N,N chelate site. The ligand results a pH-dependent sensor [77], able to detect zinc(II) ion in a neutral/slightly acidic and in a slightly basic aqueous environment with different emission responses. N,N,N tridentate complexes have a part as novel polymeric materials with intriguing structural and mechanical features for the construction of smart supramolecular architectures.…”
Section: Ligands For Sensing Analysis and For Supramolecular Architecture Buildingmentioning
confidence: 99%
“…The UV/vis characterization spectrum (figure 5) of embelin based AgNPs indicated that the absorption peak was in the spectral range at 390 nm. A broad band peaked at 390 nm was observed that can be attributed to surface plasmon resonance (Yan et al 2017). When nanoparticles are illuminated with light of a particular wavelength, the free electrons on the surface of the nanoparticles collectively oscillate in resonance with the incoming light waves, producing an enhanced electromagnetic field at the surface of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In PBI-AgNP, a new peak appears at 440 nm, along with the peak of PBI-UW molecules at the shoulder position. The peak at 440 nm is attributed to the surface plasmon resonance (SPR) of the silver nanoparticles, 41,42 which suggests the formation of a PBI-capped silver nanoparticle (dihybrid system). The graphene oxide (GO) exhibited peaks at 234 and 304 nm that are assigned to the p-p* transition and n-p* transition respectively.…”
Section: Uv-visible Studymentioning
confidence: 99%